PERBEDAAN HASIL FIKSASI ALKOHOL 96% SELAMA 15 MENIT DAN 30 MENIT PADA PEWARNAAN PAPANICOLAOU - Ajeng Sukma Rima Dani; Indah Sari (Journal of Indonesian Medical Laboratory and Science, 2022)
Cervical cancer is a cancer that apprears in the cervix caused by Human Papilloma Virus (HPV) infection. According to the World Health Organization (WHO) explains that cervical cancer is the fourth-order cancer that represents 6,6% of all cancers is women. Pap smear is an examination done to detect cervical cancer. Pap smear examination using vaginal swab examinations material that must be fixated before coloring papanicolaou. This study aims to determine the defference in alcohol fixation result 96% for 15 minutes and 30 minutes using papanicolaou coloring conducted at Dyatnitalis Anatomy Pathology Laboratory Palembang. Type of cross sectional research, with research design using intact group comparison. The sample consisted of 8 respondents each performed a fixation of alcohol 96% for 15 minutes and the next 30 minutes colored with the coloring papanicolaou. Research is conducted starting from patient preparations, examination material retrieval, examination material processing, analysis and examination result. Wilcoxon test results are known that the significant value is p = 0,024. The value obtained is p =? 0.05.The results can be concluded that there is a difference in alcohol fixation results 96% for 15 minutes and 30 minutes.